2006
DOI: 10.1007/bf02850224
|View full text |Cite
|
Sign up to set email alerts
|

Reward deficiency syndrome in obesity: A preliminary cross-sectional trial with a genotrim variant

Abstract: Obesity is the second largest preventable cause of death in the United States. Even though it was classified as a disease in 1985, traditionally, obesity has been treated primarily as a behavioral problem that requires only modifications in diet and exercise. Similar to research on obesity, clinical studies have elucidated the role of biologic and genetic factors in alcoholism and other conditions previously classified as behavioral. These studies showed that behavioral adjustments alone may not address underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…[24][25][26] Furthermore, a loss of 2.5 kg in only 80 days is quite statistically robust especially when considering guidelines from the US FDA regarding meaningful weight loss of any medically approved anti-obesity pharmaceutical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] Furthermore, a loss of 2.5 kg in only 80 days is quite statistically robust especially when considering guidelines from the US FDA regarding meaningful weight loss of any medically approved anti-obesity pharmaceutical.…”
Section: Discussionmentioning
confidence: 99%
“…24 Subsequent prospective studies have demonstrated that PCAL-103 significantly increased weight loss, decreased food cravings and binge eating, prevented weight regain after a period of fasting, and also reduced stress and enhanced general well-being. 25,26 In light of these early hypothesis-generating studies, and the paucity of research involving neurotransmitter manipulation of the brain reward system coupled with genetic polymorphic identification, we designed a pilot study to evaluate the process of DNA-customization of a nutritional solution for weight management. We carried out this experiment cognizant that larger randomized, placebo-controlled studies are warranted before any solid conclusions can be drawn from the present evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The hypersensitivity hypothesis suggests that the more reward a food generates, the more we eat, with apparently no upper limit of reward (3,19). The hypo-sensitivity or reward-deficit hypothesis suggests that increased intake of palatable food is an attempt to reach a certain reward set point by compensating for hypo-functioning reward generation, specifically for reduced mesolimbic dopamine transmission (12,32,33,48,65,77). Although the prospective studies in humans with genetically reduced dopamine signaling and the one observation in preobese obesity-prone rats suggest that genetic predisposition is an important factor in determining the response to palatable food, the contributions of these two competing hypotheses to the development of obesity, with no known genetic anomaly, is not well understood.…”
mentioning
confidence: 99%
“…Notably, of all the results and gene polymorphisms tested, only the DRD2 gene polymorphism (A1 allele) had a significant Pearson correlation with treatment days (r = 0.42, p = 0.045), so that there was a modest relationship between the occurrence of the A1 allele and the length of treatment days This 2-fold increase is a significant genotype for treatment compliance (Blum, Chen et al, 2006, 2007.…”
Section: Have We Hatched Dnacustomized Nutrition?mentioning
confidence: 96%
“…Further findings, which point to the need for additional research, using a Path Analysis (non-customized KB220Z), also indicated significant connections with anti-obesity behaviors. In a one-year cross-sectional, open trial study of 24 unscreened subjects, using an oral KB220Z variant, the following beneficial outcomes occurred: decreased stress; sleep improvement; increased energy; universal well-being; decreased cravings (sugar/carbohydrates); enhancement in mental focus/memory; enhancement in blood sugar levels; decreased food intake; decreased waist circumference; weight loss; decreased blood pressure; enhanced exercise performance; decreased drug-seeking; decreased hyperactivity; and decreased cholesterol levels (Blum, Chen et al, 2006). Although opioid medications effectively treat acute pain and help relieve chronic pain for some patients (Moore, Derry, Eccleston, & Kalso, 2013), their addiction risk presents a dilemma for healthcare providers seeking to relieve suffering, while preventing drug abuse and addiction.…”
Section: Have We Hatched Dnacustomized Nutrition?mentioning
confidence: 99%